دور قنوات Bein sports في نشر الثقافة الرياضية للجمهور الجزائري - عبد الحليم بن يحي; فضيل بن يحي; د/أدم رحمون (جامعة عمار ثليجي الاغواط, 2023)
ملخص : تهدف هذه الدراسة إلى معرفة توجه الشباب في مدينة الاغواط نحو القناة الرياضية bein sport والدور الذي تلعبه في نشر الثقافة الرياضية في اوساط الشباب . انطلاقا من التساؤل العام التالي : ما هو دور قنوات bein sport في نشر الثقافة الرياضية للجمهور الجزائري؟ تفرعت منه التساؤلين التاليين : 1- ماهي عادات وأنماط توجه الشباب - عينة الدراسة -في مشاهدة قنوات bein sport الرياضية ؟ 2- كيف تساهم قنوات bein sport الرياضية في نشر الثقافة الرياضية لدى الشباب -عينة الدراسة -؟ تكمن اهمية هذه الدراسة الوصفية في محاولة معرفة اقبال شباب مدينة الاغواط نحو قناة bein sport الرياضية . والثقافة التي يكتسبها الشباب - عينة الدراسة .وحجم استخدامهم لهذه الشبكة الرياضية . ولتحقيق اهداف هذه الدراسة الوصفية اعتمتمدنا المنهج الوصفي بالاستعانة باداة الاستبيان . طبقت على 30مفردة وزعت على شباب مدينة الاغواط المتردين للنادى الرياضي للشباب ،دار الثقافة بن كرييو . أبرز النتائج • ان الشباب يقبل على مشاهدة ومتابعة قنوات BIEN SPORTS، بنسبة كبيرة وأغلب التابعين من الشباب الجزائري - عينة الدراسة - الذي يتابع مواضيع وبرامج الباقة بنسبة كبيرة، ويرجع ذلك إلى أن هذه الباقة تتضمن قنوات عديدة بعدد 16 قناة متنوعة. • أن تميز القناة راجع إلى تميزها بالسبق الصحفي، لذلك فقنوات BIEN SPORTS تتميز بخدماتها الجيدة التي استقطبت جميع الفئات وكسبت نسب مشاهدات عالمية. • أن سبب مشاهدة قنوات BIEN SPORTS التلفزيونية من الشباب راجع لتنمية الثقافة الرياضية لديهم وهذا واضح من خلال وجود بعض الشباب الذين لديهم ثقافة رياضية لا بأس بها. كلمات مفتاحية : قنوات Bein sports - الثقافة الرياضية - الجمهور الجزائري . Summary: This study aims to understand the orientation of young people in the city of Agout towards the sports chain and the role it plays in promoting sports culture among young people. The following general question: What is the role of sports channels in the dissemination of sports culture to the Algerian public? The following questions were raised: 1- What are the habits and patterns of youth orientation - typical study - watching sport on sports channels? 2- How do sport channels contribute to the dissemination of sport culture among youth - sample study -? The importance of this descriptive study lies in trying to understand how the young Ghattat arrived at the canal. Be sporty. Culture acquired by youth - sample study. The size of their use of this sports network. In order to achieve the objectives of this descriptive study, the descriptive approach was adopted using the questionnaire. It was applied to 30 people who were distributed to young people in the reluctant town of Agut of the youth sports club, Ben Crew Cultural House. Highlights The young people agreed to watch and follow the channels BIEN SPORTS, with a large proportion of young Algerian affiliates - study samples - who follow the themes and programs of the packages in a large proportion, because this package includes many channels with 16 different channels. The channel is characterized by its journalism, so that BIEN SPORTS channels have its good services that attract all categories and gain global viewing rates. The reason young people watch BIEN SPORTS television is due to the development of their sports culture and this is demonstrated by the